From Prison to Community: Reconstructing Community Service Sentencing as Ius Constituendum in the Reform of Indonesia’s Criminal Procedure Code - Asis, Asis; Yakin, Bisma Ainul; Arhabi, Muhammad Farhan; Arifin, Muhamad Zainal (Journal of Judicial Review, 2025)
Community service sentence is a form of non-custodial punishment aimed at shifting the orientation of penal policy from a retributive approach towards a more corrective and restorative one. This type of punishment provides an opportunity for perpetrators of minor offenses to amend their wrongdoing through tangible contributions to society without having to serve imprisonment. However, to date, the regulation of community service sentencing remains legally unregulated within the Indonesian criminal procedural system, particularly in the Criminal Procedure Code (KUHAP). This legal vacuum has resulted in the absence of an adequate legal basis for judges and law enforcement officials to impose and implement such a sentence. This article aims to examine community service punishment as a form of ius constituendum, namely, law that ought to be enacted in the future, within the framework of KUHAP reform. By employing normative and conceptual approaches, this article explores the urgency, rationality, and regulatory direction of community service sentencing within the national penal system. The findings indicate that the inclusion of community service punishment in the forthcoming KUHAP is crucial to realizing a more proportional, humane penal system that aligns with the principles of corrective justice and the demands of a modern criminal justice system. This article further argues that the current legal vacuum reflects the unresponsiveness of Indonesia’s criminal justice system, and calls for a responsive legal framework in line with the theory of responsive law, ensuring that legal reforms are attuned to evolving societal needs and values of justice.